Skin measurements in relation to milking traits in Murrah buffaloes - BARATI, R; SINGH, R; FAHIM, A; SINGH, Y P; ALI, N; GUPTA, A; DAVID, B M (The Indian Journal of Animal Sciences, 2017)
There was significant effect of skin thickness on daily milk yield, milking time and milk flow rate in Murrah buffaloes. The daily milk yield was negatively correlated with skin fold thickness in these animals and significant correlations were found with skin fold thickness of flank (–0.334) and udder (–0.264) regions. The milk let down time was not affected; whereas milking time was significantly affected based on daily milk yield and milk flow rate. The milk flow rate was significantly higher for animals with thin and moderately thick skin of different body regions except abdomen (29.27±0.70 g/sec). No significant variation was seen in fat percentage based on skin thickness, except in chest region which was negatively correlated (–0.398).